An observational study of breakthrough SARS-CoV-2 Delta variant infections among vaccinated healthcare workers in Vietnam. (November 2021) - Chau, Nguyen Van Vinh; Ngoc, Nghiem My; Nguyet, Lam Anh; Quang, Vo Minh; Ny, Nguyen Thi Han; Khoa, Dao Bach; Phong, Nguyen Thanh; Toan, Le Mau; Hong, Nguyen Thi Thu; Tuyen, Nguyen Thi Kim; Phat, Voong Vinh; Nhu, Le Nguyen Truc; et al.
ABSTRACT: Background: Data on breakthrough SARS-CoV-2 Delta variant infections in vaccinated individuals are limited. Methods: We studied breakthrough infections among Oxford-AstraZeneca vaccinated healthcare workers in an infectious diseases hospital in Vietnam. We collected demographic and clinical data alongside serial PCR testing, measurement of SARS-CoV-2 antibodies, and viral whole-genome sequencing. Findings: Between 11 th –25 th June 2021 (7-8 weeks after the second dose), 69 staff tested positive for SARS-CoV-2. 62 participated in the study. Most were asymptomatic or mildly symptomatic and all recovered. Twenty-two complete-genome sequences were obtained; all were Delta variant and were phylogenetically distinct from contemporary viruses obtained from the community or from hospital patients admitted prior to the outbreak. Viral loads inferred from Ct values were 251 times higher than in cases infected with the original strain in March/April 2020. Median time from diagnosis to negative PCR was 21 days (range 8–33). Neutralizing antibodies (expressed as percentage of inhibition) measured after the second vaccine dose, or at diagnosis, were lower in cases than in uninfected, fully vaccinated controls (median (IQR): 69.4 (50.7-89.1) vs. 91.3 (79.6-94.9), p=0.005 and 59.4 (32.5-73.1) vs. 91.1 (77.3-94.2), p=0.043). There was no correlation between vaccine-induced neutralizing antibody levels and peak viral loads or the development of symptoms. Interpretation: Breakthrough Delta variant infections following Oxford-AstraZeneca vaccination may cause asymptomatic or mild disease, but are associated with high viral loads, prolonged PCR positivity and low levels of vaccine-induced neutralizing antibodies. Epidemiological and sequence data suggested ongoing transmission had occurred between fully vaccinated individuals. Funding: Wellcome and NIH/NIAID